Functional Attenuation of UCP1 as the Potential Mechanism for a Thickened Blubber Layer in Cetaceans. (27th October 2022) - Zhou, Ming; Wu, Tianzhen; Chen, Yue; Xu, Shixia; Yang, Guang
Abstract: Uncoupling protein 1 ( UCP1 ) is an essential protein in the mitochondrial inner membrane that mediates nonshivering thermogenesis (NST) and plays an important role in thermoregulation and fat deposition. However, the relationship between the evolution of UCP1 and fat deposition in the blubber layer in cetaceans remains unclear. Here, frameshift mutations, premature termination, and relaxed selection pressure ( ω = 0.9557, P < 0.05) were detected in UCP1 in cetaceans, suggesting that UCP1 was inactivated during cetacean evolution. By time estimation, it was found that the inactivation of UCP1 in cetaceans occurred between 53.1 and 50.2 Ma. However, combined with findings from immunohistochemical analysis of the blubber layer of the Yangtze finless porpoise and in vitro functional assays, a premature termination of cetacean UCP1 resulted in a reduction of UCP1 -mediated NST capacity (about 50%) and lipolytic capacity (about 40%), both of which were beneficial to maintain blubber layer and body temperature without excessive fat consumption. This study provides new insights into the molecular mechanisms of the blubber thickening in cetaceans and highlights the importance of UCP1 attenuation in cetaceans for secondary aquatic adaptation.